2012
DOI: 10.1111/tbj.12046
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Age and HRT Use with Breast Density as Assessed by Quantra

Abstract: Breast density is a significant predictor in the risk of developing breast cancer. Several methods are available for assessing breast density, but most are subject to intra-observer variability and are unable to assess the breast as a three-dimensional structure. Using Quantra(™) to quantify breast density, we have correlated this with risk factors to determine what impact these variables have on breast density. Women attending for full field digital mammography at the South West London Breast Screening Unit b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
0
23
2
Order By: Relevance
“…Standardized and calibrated approaches have given mixed results in producing a measure that provides equivalent or stronger breast cancer associations than given by PD (17, 20, 42-44, 47, 48). There are commercial products available that use standardized data for estimating breast density from raw FFDM images including studies that show their comparison with the clinical BI-RADS density measure (21, 22) and other risk factors (23). But, to date, there are no published data that demonstrates their association with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized and calibrated approaches have given mixed results in producing a measure that provides equivalent or stronger breast cancer associations than given by PD (17, 20, 42-44, 47, 48). There are commercial products available that use standardized data for estimating breast density from raw FFDM images including studies that show their comparison with the clinical BI-RADS density measure (21, 22) and other risk factors (23). But, to date, there are no published data that demonstrates their association with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There are various methods under development to automate the estimation of breast density (4-21). Developing a fully automated and standardized breast density measurement has proven somewhat difficult, but at least two commercial standardized measures are available for raw FFDM images, Volpara and Quantra (19, 21-23). However, these have not been shown to be associated with breast cancer risk to date.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Others are automated thresholding approaches, such as Autodensity and MedDensity, 25,26 and three physical model-based techniques: standard mammographic form (SMF), Volpara and Quantra. [27][28][29] Irrespective of the method of measurement, breast density has been shown to be a potent risk factor for breast cancer.…”
mentioning
confidence: 99%
“…In addition to their feasibility proven by several studies [36][37][38], they have been reported to be effective for assessing breast cancer risk derived from breast density [39]. Brand et al [40] evaluated the performance of a fully automated volumetric method (Volpara), which is capable of calculating volumetric breast density out of raw mammogram imaging data, regardless of the mammography system used.…”
Section: Volumetric Breast Density Measuring Applicationsmentioning
confidence: 99%